Histamine Stimulates Ciliary Beat Frequency via the H2 Receptor in the Protochordate Botryllus schlosseri. Issue 3 (3rd May 2016) - Cima, Francesca; Franchi, Nicola
ABSTRACT: Histamine is a biogenic molecule that plays a role in many physiological pathways via binding to a specific receptor. Histaminergic receptors belong to the large family of seven‐transmembrane α‐helix domain receptors classified in mammals into four distinct classes: H1, H2, H3, and H4. Despite being widely studied in vertebrates, few data are available on the invertebrate receptors, with only predicted H1 and H2 sequences for nonchordate deuterostomes. Here, we report the first characterized transcript sequence for an H2 receptor from the colonial ascidian Botryllus schlosseri, describing the localization of both transcript and protein during blastogenic development through in situ hybridization and immunohistochemistry. Its phylogenetic relationships with deuterostome orthologous proteins are reported, its role in ciliary beat frequency (CBF) in cultured stigma cells of the branchial basket is outlined, and the effects of histamine and its receptor agonists and antagonists are analyzed. In the presence of increasing concentrations of histamine in the medium, CBF increases similarly to the selective H2 receptor agonist dimaprit. In contrast, ranitidine, which is an inhibitor of the H2 receptor, causes a significant inhibition of CBF, similar to that observed after preincubation with the specific anti‐BsHRH2 or the anti‐human HRH2 antibody. In cells bordering the branchial basket stigmata, both antibodies colocalize in the proximal region of the ciliary plasmalemma, and histamine is present inside vesicles of the apical region, thus supporting the hypothesis of a histamine‐binding H2 receptor control of the pharyngeal mucociliary transport similar to that of the upper respiratory tract and middle ear in mammals.